Fewer politicians and smaller assemblies: how party elites rationalise reducing the number of seats in a legislature – lessons from Canada. Issue 2 (3rd April 2019) - Marland, Alex
ABSTRACT: Scholars are unable to rationalise the number of elected representatives in legislative assemblies. This study offers some insights into the political arithmetic by examining the rare event of reducing seats in a legislature. It is hypothesised that a policy of cutting electoral districts occurs during a search for cost efficiencies and a burst of populism. Interviews with party elites involved with seven seat reduction events in Canadian provinces establishes that the primary reason for the policy is its symbolic value. The message of fewer politicians sets an example for belt-tightening across government that will assist the executive branch with its austerity agenda. In these situations, the final number of members of a legislature matters little to a cabinet and most legislators compared with the broader symbolism of a smaller legislative branch.